PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA DENGAN FASILITAS KERJA SEBAGAI MEDIASI PADA KANTOR DESA PEBENAAN - M. Akasah; Donal Devi Amdanata (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The purpose of this research is to determine the influence of compensation on job satisfaction, the influence of compensation on employee work facilities, and the influence of compensation on employee job satisfaction with work facilities as a mediator at Pebenaan Village Office. 33The population in this study consisted of 63 employees and officials of Pebenaan Village Office. The sampling technique used non-probability sampling method (non- random sample), namely the Saturated Sampling Technique, which involves the entire population as the sample. The statistical methods used were descriptive statistics for descriptive analysis and the Structural Equation Model (SEM) to test the research hypotheses using SmartPLS 4 software. The results of the study indicate a significant influence of compensation on job satisfaction among officials at Pebenaan Village Office, a significant influence of compensation on work facilities among officials at Pebenaan Village Office, no influence of work facilities on job satisfaction among officials at Pebenaan Village Office, and no influence of compensation on job satisfaction with work facilities as a mediating variable among officials at Pebenaan Village Office.